2013
DOI: 10.3762/bjoc.9.308
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in the mechanistic understanding of the copper-catalyzed azide–alkyne cycloaddition

Abstract: SummaryThe copper-catalyzed azide–alkyne cycloaddition (CuAAC) is one of the most broadly applicable and easy-to-handle reactions in the arsenal of organic chemistry. However, the mechanistic understanding of this reaction has lagged behind the plethora of its applications for a long time. As reagent mixtures of copper salts and additives are commonly used in CuAAC reactions, the structure of the catalytically active species itself has remained subject to speculation, which can be attributed to the multifacete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
139
0
14

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(156 citation statements)
references
References 199 publications
2
139
0
14
Order By: Relevance
“…Since the early reports, a variety of transition-metal catalysts have been used for the reactions between mono-or disubstituted alkynes and azides (vide infra). For the Cu(I) catalyzed reaction, a variety of mechanisms involving Cu(I)-aryl intermediates have been proposed in which the key-step species contains either mononuclear [35] or binuclear copper species [30][31][32][33][34][35][36][37][38]. Theoretical studies of the RuAAC reaction have also been reported [28,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Since the early reports, a variety of transition-metal catalysts have been used for the reactions between mono-or disubstituted alkynes and azides (vide infra). For the Cu(I) catalyzed reaction, a variety of mechanisms involving Cu(I)-aryl intermediates have been proposed in which the key-step species contains either mononuclear [35] or binuclear copper species [30][31][32][33][34][35][36][37][38]. Theoretical studies of the RuAAC reaction have also been reported [28,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Cu-promoted coupling reactions have been extensively used for the synthesis of several molecules and biomolecules. [9][10][11] The azidation reaction has been used as a facile method for the transformation of an aryl halide into an aryl azide. Synthetic applications of these ar-…”
Section: Introductionmentioning
confidence: 99%
“…Так, двойные связи могут быть легко функционализированы реакцией радикаль-ного присоединения тиолов, [5,6] а тройные -путем медь(I)-катализируемого циклоприсоединения 1,3-диполей. [7][8][9][10][11] Несмотря на большое разнообразие исследований в химии каликсаренов и их тиа-аналогов, публикации, где были бы получены бифункциональные каликсарены, содержащие двойные и тройные терминальные связи, отсутствуют.…”
Section: Introductionunclassified